Two echinoid species from the early Aptian (Early Cretaceous) of the Kopet-Dagh Basin, NE Iran - Schlüter, Nils; Taherpour-Khalil-Abad, Morteza; Majidifard, Mahmoudreza; Hassanzadeh, Zinat; Taheri, Jafar (Zootaxa, 2019)
Two echinoid species from the Sarcheshmeh Formation, early Aptian, Lower Cretaceous, of the Kopet-Dagh Basin, NE Iran, are described: a phymosomatoid specimen of Tetragramma sp., and the spatangoid echinoid Miotoxaster collegnii (Sismonda, 1844). This is the first report of echinoids from the Sarcheshmeh Formation from northeastern Iran.